SUSTAINED VIROLOGIC RESPONSE RATE IN CHRONIC HEPATITIS C PATIENTS THROUGH DIRECT-ACTING ANTIVIRALS THERAPY - TORRES,Andréa Delfino (2019)
ABSTRACT BACKGROUND: In recent years the management of hepatitis C virus infection and the possibility of its eradication have been researched due to the importance that they represent in the health of the world population. Obtaining data that help to cope with this pathology improves the quality of life of those affected by it. The present study evaluated the effectiveness of direct-acting antiviral therapies provided by the Brazilian Ministry of Health in accordance to the Clinical Protocol and Therapeutic Guidelines of 2015. OBJECTIVE: To evaluate the epidemiological profile of patients with chronic hepatitis C and the rate of sustained virologic response using direct-acting antivirals of all individuals that attended the referral service for the treatment of chronic hepatitis C at the Hospital of the Federal University of Rio Grande. METHODS: This was an observational, retrospective/prospective study with all patients with chronic hepatitis C who had their treatments available from December 2015 to August 2017 according to the criteria of the Clinical Protocol and Therapeutic Guidelines of 2015. In the first phase, the clinical and demographic variables of all individuals enrolled in a treatment for hepatitis C were selected and collected from the Reference Service database. In the second phase, treatment data were collected. The outcome variable, sustained virologic response, was defined as an undetectable viral load on the blood test three months after the end of treatment. The descriptive and bivariate analyzes were performed with Pearson’s chi-square and Fisher’s Exact test, adopting a P value ≤0.05 in the SPSS 20 software. RESULTS: Of the 252 participants in the study, 228 (90.5%) had a sustained virologic response, 55.2% were male with an average age of 58.6 years (SD±9.1). Genotype 1 was the most prevalent, observed in 54.4% of the participants, and 87.4% of the patients had moderate/advanced hepatic fibrosis. After the statistical analysis, it was observed that the individuals with genotype 3 and moderate/advanced hepatic fibrosis had lower sustained virologic response rate (P=0.05 and P=0.04, respectively). CONCLUSION: It was observed that the use of direct-acting antivirals, in comparison to previous therapeutic regimens, increases the sustained virologic response, reaching all patients with mild fibrosis. This study provides information that helps in the hepatitis C treatment by showing that prescribing early treatment for patients without hepatic fibrosis and/or genotype 3 virus could increase therapeutic effectiveness.